Pengaruh DER, ROA, dan DPR Terhadap Return Saham Sektor Utilitas, Insfrastruktur, dan Transportasi. - Nova Dwi Andriyanto; Alfiatul Maulida; Sri Hermuningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Stock return is one of the triggers in the investment process, stock returns are often used as a measurement tool by investors in making comparisons of investment alternatives, this can help investors to know the company's success before investing. The purpose of this study is to examine and analyze empirically the effect of Debt to Equity Ratio, Return On Assets, Dividend Payout Ratio on stock returns. The selection of scientific study data is collected by companies on the Indonesia Stock Exchange for the 2015-2020 period. The sample collection technique used is purposive sampling technique, with only 9 (nine) companies that meet the analysis criteria using the classical assumption test and multiple linear regression analysis techniques using SPSS 21 software. This is according to the classical assumption test and the fit test of the regression model which results in a data that can be used for analysis. The conclusion of the study shows that Return on Assets is able to influence positively and significantly, while the Debt to Equity Ratio and Dividend Payout Ratio have no effect on stock returns. Keywords: Debt to equity ratio;Return On Assets; Dividend Payout Ratio; Stock return.